Patients Receiving Correctional Assistance At Class 1 Rutan Clinic In Central Jakarta's Knowledge Of Covid-19 Prevention And Review From An Islamic Perspective - Amara Nurul Afifah; Edward Syam; Muhammad Arsyad (Junior Medical Journal, 2022)
Background: A novel variety of coronavirus is what causes Coronavirus Sickness-2019 (Covid-19), a disease. Cough, fever, exhaustion, breathlessness, and lack of appetite are signs of the Covid-19 infection. In order to prevent the corona virus from spreading further, the WHO refers to physical separation as a physical distance regulation. To be able to stop the spread of COVID-19, research on COVID-19 awareness among patients receiving correctional assistance at the Class 1 Rutan Clinic in Central Jakarta is deemed crucial.Method: This kind of study employs cross-sectional research methodology and descriptive observation. 2,900 patients receiving correctional assistance made up the study's sample of 352 participants, who were seen at the Class 1 Rutan Clinic in the heart of Jakarta. Techniques for gathering data include surveys and one-on-one interviews with respondents. Bivariate and univariate analysis are the methods used in this study.Result: Features of the 352 respondents, including 89 (25.28%) respondents who were between the ages of 24 and 29. As many as 281 (79.8%) respondents reported that they had never heard of COVID-19. 66% of the 233 respondents have high knowledge and preventative skills. There is a correlation between the Knowledge Level of Prevention and the Incidence of COVID-19, according to the findings of the Chi-Square statistical test, which yielded the Continuity Correction value = 0.049 where p0.05.Conclusion: The Class 1 Central Jakarta Rutan Clinic classifies the level of COVID-19 prevention knowledge among patients receiving correctional assistance as